ASSISTANCE FOR THE DEVELOPMENT OF THE "BUMDES INSTITUTE PLATFORM LEARNING" APPLICATION IN PANDEMAS MULYA VILLAGE, KABUTEN MALANG - Hanifa Maulani Ramadhan; Wilopo; Inggang Perwangsa Nuralam; Safarudin Hisyam Tualeka; Rizal Alfisyahr (Berdikari: Jurnal Pengabdian Masyarakat Indonesia, 2022)
Introduction: Badan Usaha Milik Desa or BUMDes in Government Regulation Number 11 of 2021 concerning BUMDes are legal entities established by villages or with villages to manage businesses, utilize assets, develop investment and productivity, provide services, or provide other types of companies. For the most excellent welfare of the village community. In its application, BUMDes (which in this study is "BUMDes Pandemas Mulya") is expected to be able to collaborate with stakeholders and other parties such as investors, communities, and the people to form a so-called Penta helix so that the capacity and capability of the BUMDes can increase significantly. However, in reality, BUMDes still need to catch up to the target set by the Ministry. Therefore, a tool was created that can increase the capacity and capability of BUMDes itself by utilizing digital technology called "BUMDes Institute Platform Learning." Method: In general, the implementation of creating the "BUMDes Institute Platform Learning" platform is divided into four stages: Needs Analysis, Mapping problems, Validating problems, and Designing applications. The Needs Analysis stage aims to identify issues and material needs for BUMDes actors that will be accommodated in the platform. The needs analysis results are then carried out through a mapping process based on predetermined criteria. The goal is to create clusters between problems and solutions in the form of learning materials that will be included in the platform. Next, the team will validate the results of the problem-mapping process in the validation stage. Then, the team conducts FGDs and internal discussions for the collection process materials to create a learning curriculum and requirements for the application design and development process. After that, the development begins. Results: the application can be implemented for BUMDes even though several improvements will be needed. Conclusions: BUMDes Pandemas Mulya still needs much improvement to develop business units, especially related to business design. So, there needs to be an application that contains information from technical aspects for management (application program) conditions in the field still need completion and periodic assistance that can help educate and teach business aspects.